Mri Assessment of Cerebral Blood Flow after Experimental Traumatic Brain Injury Combined with Hemorrhagic Shock in Mice. Issue 1 (January 2013) - Foley, Lesley M; O'Meara, Alia M Iqbal; Wisniewski, Stephen R; Hitchens, T Kevin; Melick, John A; Ho, Chien; Jenkins, Larry W; Kochanek, Patrick M
Secondary insults such as hypotension or hemorrhagic shock (HS) can greatly worsen outcome after traumatic brain injury (TBI). We recently developed a mouse combined injury model of TBI and HS using a controlled cortical impact (CCI) model and showed that 90 minutes of HS can exacerbate neuronal death in hippocampus beneath the contusion. This combined injury model has three clinically relevant phases, a shock, pre hospital, and definitive care phases. Mice were randomly assigned to four groups, shams as well as a CCI only, an HS only, and a CCI + HS groups. The CCI and HS reduced cerebral blood flow (CBF) in multiple regions of interest (ROIs) in the hemisphere ipsilateral and contralateral to injury. Hemorrhagic shock to a level of ~30 mm Hg exacerbated the CCI-induced CBF reductions in multiple ROIs ipsilateral to injury (hemisphere and thalamus) and in the hemisphere contralateral to injury (hemisphere, thalamus, hippocampus, and cortex, all P < 0.05 versus CCI only, HS only or both). An important effect of HS duration was also seen after CCI with maximal CBF reduction seen at 90 minutes ( P < 0.0001 group-time effect in ipsilateral hippocampus). Given that neuronal death in hippocampus is exacerbated by 90 minutes of HS in this model, our data suggest an important role for exacerbation of posttraumatic ischemia in mediating the secondary injury in CCI plus HS. In conclusion, the serial, non invasive assessment of CBF using ASL-MRI (magnetic resonance imaging with arterial spin labeling) is feasible in mice even in the complex setting of combined CCI + HS. The impact of resuscitation therapies and various mutant mouse strains on CBF and other outcomes merits investigation in this model.